Non-active antibiotic and bacteriophage synergism to successfully treat recurrent urinary tract infection caused by extensively drug-resistant Klebsiella pneumoniae. Issue 1 (1st January 2020) - Bao, Juan; Wu, Nannan; Zeng, Yigang; Chen, Liguang; Li, Linlin; Yang, Lan; Zhang, Yiyuan; Guo, Mingquan; Li, Lisha; Li, Jie; Tan, Demeng; Cheng, Mengjun; et al.
ABSTRACT: We report a case of a 63-year-old female patient who developed a recurrent urinary tract infection (UTI) with extensively drug-resistant Klebsiella pneumoniae (ERKp). In the initial two rounds of phage therapy, phage resistant mutants developed within days. Although ERKp strains were completely resistant to sulfamethoxazole-trimethoprim, the combination of sulfamethoxazole-trimethoprim with the phage cocktail inhibited the emergence of phage resistant mutant in vitro, and the UTI of patient was successfully cured by this combination. Thus, we propose that non-active antibiotic and bacteriophage synergism (NABS) might be an alternative strategy in personalized phage therapy.